Therapeutic Aspects of Hydrotherapy: A Review - Chowdhury, Ranajit Sen; Islam, Md Daharul; Akter, Khaleda; Sarkar, Mohammad Abdus Sattar; Roy, Tanima; Rahman, SM Tajdit (Bangladesh Journal of Medicine, 2021)
Hydrotherapy is a procedure where water of different temperatures are used to relieve pain and treat illness. This review describes about different conditions of water treatments. Hydrotherapy can help treat a variety of conditions, including arthritis, stomach problems, sleep disorders, stress and depression. The theory behind hydrotherapy is that water has healing properties that can mitigate various ailments and conditions. Different states of water such as ice, liquid, and steam is used in the treatment of various conditions. Water cure therapies comprise enema therapy, gel therapy etc. and also includes colonic hydrotropic, sitz bath, hydro-massage, wraps and compress methods. Cryotherapy, cold water immersion or ice bath could be a new treatment method thatis used by physical therapists, sports medicine facilities and rehab clinics. Bangladesh J Medicine July 2021; 32(2) : 138-141